2008
DOI: 10.33584/jnzg.2008.70.2704
|View full text |Cite
|
Sign up to set email alerts
|

Survey of management practices of dairy cows grazing kale in Canterbury

Abstract: Many dairy cows, particularly in southern New Zealand have kale (Brassica olercaea) as a major component of their winter diet. Anecdotal evidence suggests variable results in cow body condition are achieved when kale is used as a component of the winter diet. A survey of crop yield, nutritive value and grazing management practices of kale crops was undertaken in Canterbury during winter 2007 to investigate possible causes of these variable results. Keywords: kale, utilisation, allowance, quality, dairy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
19
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 2 publications
6
19
2
Order By: Relevance
“…The high DM utilization of kale is consistent with other studies (Keogh et al, 2009b;Rugoho et al, 2014), but above the mean of 80% found in a survey of dairy cows herds in Canterbury (Judson and Edwards, 2008). The lower DM utilization of grass probably reflects an ungrazeable barrier of grass sheath and stem material at the base of the canopy.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The high DM utilization of kale is consistent with other studies (Keogh et al, 2009b;Rugoho et al, 2014), but above the mean of 80% found in a survey of dairy cows herds in Canterbury (Judson and Edwards, 2008). The lower DM utilization of grass probably reflects an ungrazeable barrier of grass sheath and stem material at the base of the canopy.…”
supporting
confidence: 90%
“…As a result, we found no evidence that offering kale or grass twice a day leads to greater utilization as a result of wide and shallow breaks, which are thought to reduce trampling under wet soil conditions during winter. Judson and Edwards (2008) suggested that the high utilization of kale would potentially result in reduced diet quality as stem of lower ME content is included into the diet. This would particularly be the case for high-yielding crops of giant type cultivars, such as 'Gruner,' with a higher stem-to-leaf ratio (e.g., 80% stem; Chakwizira et al, 2015).…”
mentioning
confidence: 99%
“…The increase in NO 3 –N concentration along the stem length, from the top to bottom of the stem (Figure ) means that the current push for high feed utilization (Judson and Edwards, ) may force the animals to graze most of the bottom stem, thereby inadvertently exposing them to the highest NO 3 –N concentrations in the plant. There is a need therefore to find a balance between acceptable feed utilization and exposing animals to nitrate poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of potential sources of error when estimating an average feed intake, including accuracy of crop or pasture yield assessments, errors in field area or grazing days, uncertainty of supplementary feed allocation, or under/over estimation of feed utilisation. A survey of dry cows grazing kale in Canterbury, NZ revealed that DMI is typically lower than targeted by farmers, which the authors attributed to inaccuracy in feed allocation (Judson & Edwards 2008). Supplementary feed wastage can range from 4 to 46% in good weather conditions, and is increased in wet weather and with increasing feed allocation (Stockdale 2010), so the 88% utilisation estimated by surveyed farmers here may be an over estimation, although the mean crop utilisation of 83% is similar to the 80% reported by Judson and Edwards (2008).…”
Section: Figurementioning
confidence: 99%
“…A survey of dry cows grazing kale in Canterbury, NZ revealed that DMI is typically lower than targeted by farmers, which the authors attributed to inaccuracy in feed allocation (Judson & Edwards 2008). Supplementary feed wastage can range from 4 to 46% in good weather conditions, and is increased in wet weather and with increasing feed allocation (Stockdale 2010), so the 88% utilisation estimated by surveyed farmers here may be an over estimation, although the mean crop utilisation of 83% is similar to the 80% reported by Judson and Edwards (2008). More accurate feed allocation combined with Lwt monitoring may help improve heifer performance on farms.…”
Section: Figurementioning
confidence: 99%